Teaching Stethoscope - Palaniappan, Sivakumar (Universiti Sains Malaysia, 2005)
Teaching Stethoscope is one of the latest biomedical gadgets which have been constructed in this project. This project is implemented by constructing hardware and software design. Basically, this project is divided into three categories which are signal amplification, wireless transmission and computer display. The components that involve in constructing hardware are stethoscope, microphone, instrumentation amplifier, buffer, integrator, low pass filter, audio amplifier and speaker. This part is the heart of the project whereby the signal will be captured through microphone and amplified with the instrumentation amplifier. It will be then filtered by an integrator and low-pass circuit below 200 Hz to reduce the noise. There will be two approaches of displaying the signal in the computer which is MATLAB and Microcontroller 89C51. This analog signal will be converted to digital signal by ADC before it is sent to the microcontroller. By using microcontroller 89C51 as data connection heart pulse are shown in LABVIEW software. The second option will be connecting the hardware to computer through microphone jack and display it through MATLAB in a pulse form. Wireless transmission involves the implementation of FM transmitter and FM receiver. Finally, output signal from the FM receiver will be amplified by using audio amplifier to be heard through the speaker.